The steel kiss ebook - Deaver, Jeffery (Lincoln Rhyme, 2016)
New York Times bestselling author Jeffery Deaver returns with his next blockbuster thriller featuring forensic detective Lincoln Rhyme. Amelia Sachs is hot on the trail of a killer. She's chasing him through a department store in Brooklyn when an escalator malfunctions. The stairs give way, with one man horribly mangled by the gears. Sachs is forced to let her quarry escape as she jumps in to try to help save the victim. She and famed forensic detective Lincoln Rhyme soon learn, however, that the incident may not have been an accident at all, but the first in a series of intentional attacks. They find themselves up against one of their most formidable opponents ever: a brilliant killer who turns common products into murder weapons. As the body count threatens to grow, Sachs and Rhyme must race against the clock to unmask his identity—and discover his mission—before more people die.